'Moixent', an Apricot Resistant to Sharka - Martínez-Calvo, José; Llácer, Gerardo; Badenes, María L. (2017)
‘Moixent’ is a self-compatible, earlyripening apricot cultivar (Prunus armeniaca L.) with excellent fruit quality and resistance to sharka (plum pox virus), a serious disease limiting apricot fruit production in affected areas. ‘Moixent’ fruits have excellent organoleptic characteristics, significantly improved from other early cultivars available in themarket. ‘Moixent’ is well adapted to areas with warm winter and Mediterranean climate and presents good fruit set and productivity.